Complete Renal Duplication with Dysplastic Lower Moiety: A Case Report - Fateme Guitynavard (Urology Research Center, 2020)
Introduction Ureter duplication is a common anomaly of the urinary tract in which both ureters drain one kidney. In bipolar renal duplication, the Meyer-Weigert-Rule describes the duplex ureters draining pattern. Owing to obstruction, the upper pole is usually seen as dysplastic, while the lower pole is associated with vesicoureteral reflux. Case presentation Herein, we report a rare case of renal duplication in which the lower moiety is dysplastic. A 30-year-old woman with a right single kidney with atrophic and dysfunction without secretions. Conclusions Radiologists and urologists should always be aware because if the lower moiety is obstructive, this newly implemented variation can require individualized care.